Ionotropic receptors mediate olfactory learning and memory in Drosophila. - Ali, M.Z.; Anushree,; Ahsan, A.; Ola, M.S.; Haque, R.; Ahsan, J. (Insect Science, 2024)
Phenylacetaldehyde (PAH), an aromatic compound, is present in a diverse range of fruits including overripe bananas and prickly pear cactus, the two major host fruits for Drosophila melanogaster. PAH acts as a potent ligand for the ionotropic receptor 84a (IR84a) in the adult fruit fly and it is detected by the IR84a/IR8a heterotetrameric complex. Its role in the male courtship behavior through IR84a as an environmental aphrodisiac is of additional importance. In D. melanogaster, two distinct kinds of olfactory receptors, that is, odorant receptors (ORs) and ionotropic receptors (IRs), perceive the odorant stimuli. They display unique structural, molecular, and functional characteristics in addition to having different evolutionary origins. Traditionally, olfactory cues detected by the ORs such as ethyl acetate, 1-butanol, isoamyl acetate, 1-octanol, 4-methylcyclohexanol, etc. classified as aliphatic esters and alcohols have been employed in olfactory classical conditioning using fruit flies. This underlines the participation of OR-activated olfactory pathways in learning and memory formation. Our study elucidates that likewise ethyl acetate (EA) (an OR-responsive odorant), PAH (an IR-responsive aromatic compound) too can form learning and memory when associated with an appetitive gustatory reinforcer. The association of PAH with sucrose (PAH/SUC) led to learning and formation of the long-term memory (LTM). Additionally, the Orco[1], Ir84a[MI00501], and Ir8a[1] mutant flies were used to confirm the exclusive participation of the IR84a/IR8a complex in PAH/SUC olfactory associative conditioning. These results highlight the involvement of IRs via an IR-activated pathway in facilitating robust olfactory behavior.